The East African Community trade report 2007 - EAC (EAC, 2008)
The 2007 report builds on the 2006 report that provided an analysis of trade amongst Kenya, Uganda and Tanzania, and to some extent Burundi and Rwanda and the rest of the world. A deeper analysis has now been undertaken although Rwanda and Burundi will commence application of the main EAC Customs Union instruments in July 2009. The report is structured in 8 chapters starting with an introduction in Chapter one followed by macroeconomic developments at international and regional level. Chapter 2 and Chapter 3 discuss the trade developments among the EAC Partner States and other regions. Chapter 4 and 5 deals with trade developments of the respective EAC Partner States and special category consideration within EAC Customs Union respectively. Chapter 6 is a review of customs revenue performance in the Partner States. Chapter 7 reviews the performance of investment flows in the region in relation to the rest of the world. Chapter 8 provides the conclusion and way forward.
Keywords: Customs Union; Customs Revenue; Trade; Trade Development; Trade Performance